Dissociative recombination and excitation of CH5+: Absolute cross sections and branching fractions - Semaniak, J; Larson, A; Le Padellec, A; Stromholm, C; Larsson, M; Rosen, S; Peverall, R; Danared, H; Djuric, N; Dunn, G; Datz, S (Institute of Physics Publishing, 1998)
The heavy-ion storage ring CRYRING was used to measure the absolute dissociative recombination and dissociative excitation cross sections for collision energies below 50 eV. Deduced thermal rates coefficients are consistent with previous beams data but are lower by a factor of 3 than the rates measured by means of the flowing afterglow Langmuir probe technique. A resonant structure in dissociative recombination cross section was found at 9 eV. We have determined the branching fractions in DR of CH5+ below 0.2 eV. The branching is dominated by three-body CH3 + H + H and CH2 + H2 + H dissociation channels, which occur with branching ratios of ≈0.7 and ≈0.2, respectively; thus methane is a minor species among dissociation products. Both the measured absolute cross sections and branching in dissociative recombination of CH5+ can have important implications for the models of dense interstellar clouds and abundance of CH2, CH3 and CH4 in these media. © 1998. The American Astronomical Society. All rights reserved.